2004
DOI: 10.1086/423927
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Mass Donor Star’s Spectrum in SS 433

Abstract: We present spectroscopy of the microquasar SS 433 obtained near primary eclipse and disk precessional phase Ψ = 0.0, when the accretion disk is expected to be most "face-on". The likelihood of observing the spectrum of the mass donor is maximized at this combination of orbital and precessional phases since the donor is in the foreground and above the extended disk believed to be present in the system. The spectra were obtained over four different runs centered on these special phases. The blue spectra show cle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
143
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(156 citation statements)
references
References 32 publications
(41 reference statements)
12
143
1
Order By: Relevance
“…In order to get a black body emission negligible compared to this optically thin emission, we had to set the radius of the A7 I star to R = 30 R or less. Then this constraint is compatible with the result of Hillwig et al (2004), who find the radius of the Roche lobe volume for the mass donor star to be R L = 28 ± 2 R . Note that this corresponds to a star with an intermediate size between type I (supergiant) and type II (bright giant) stars (Venn 1995).…”
Section: Nature Of the Donor Star And Mid-ir Constraintssupporting
confidence: 87%
See 2 more Smart Citations
“…In order to get a black body emission negligible compared to this optically thin emission, we had to set the radius of the A7 I star to R = 30 R or less. Then this constraint is compatible with the result of Hillwig et al (2004), who find the radius of the Roche lobe volume for the mass donor star to be R L = 28 ± 2 R . Note that this corresponds to a star with an intermediate size between type I (supergiant) and type II (bright giant) stars (Venn 1995).…”
Section: Nature Of the Donor Star And Mid-ir Constraintssupporting
confidence: 87%
“…Note that Hillwig et al (2004) find a binary separation of a = 0.26 ± 0.02 AU = 56 ± 4 R , which is of the order of the typical radius of the free-free emitting region at 5 µm R 5 µm = 50−67 R , which we calculated in Sect. 4.5.…”
Section: A Phenomenon Imitating a Wolf-rayet Starmentioning
confidence: 57%
See 1 more Smart Citation
“…These authors present spectra of SS 433 that show features found in an A-type supergiant but that do not follow a coherent orbital radial velocity curve. Their observations show a larger scatter, were performed over a greater variety of orbital and precessional phases, and have a much lower average velocity than those presented by Hillwig et al (2004). Barnes et al (2006) and Clark et al (2007) suggest that these A-type supergiant absorption lines arise in an accretion-driven outflow.…”
Section: Introductionmentioning
confidence: 89%
“…Finding these lines is difficult, not only due to the small relative flux contribution of the mass donor star but also to the active emission spectrum from the accretion disk, jets, and strong disk wind in the system. The most convincing observations to date of the mass donor spectrum were obtained by Hillwig et al (2004). Their spectra suggested that the donor star has a spectral classification of A3-7 I, and their radial velocity measurements led to component masses of M p O and (where the subscripts 10.9 ‫ע‬ 3.1 M M p 2.9 ‫ע‬ 0.7 M represent the optical companion star O and the X-ray-emitting compact object X).…”
Section: Introductionmentioning
confidence: 99%